Dedioxygenative Phosphonylation of Carboxylic Acids - Xiaoqiang Wu; Ruining Bai; Abuduwaili Alimu; Ting Han; Tao Xu (Journal of the American Chemical Society, 2026)
Abstract Dedioxygenative transformations of carboxylic acids are faced with the significant challenges in efficiently breaking multiple C–O bonds and achieving broad applicability across diverse carboxylic acids, thereby hampering the development and application of this field. In this work, through the cooperation of multiple catalysts, we realized a dedioxygenative phosphonylation of carboxylic acids that is applicable to both aliphatic and aromatic substrates, showing good scope and functional-group tolerance. This protocol also demonstrates promising performance in the late-stage modification of complex molecules. Meanwhile, it establishes a formal deoxygenative coupling approach that enables rapid access to alkenes from carboxylic acids and aldehydes or alcohols. Mechanistic studies reveal distinct activation modes for different C–O bonds and further highlight a carbon-retentive transformation pattern of carboxylic acids, complementing conventional carbon-deletion decarboxylative phosphonylation based on redox-active esters or other strategies.